Ultrasound's Impact on Preclinical Medical Student Neurology Unit Grades: Findings After 2 Years. (1st December 2020) - Shah, Varun S.; Allman, Alexandra; Verbeck, Nicole; Quinn, Melissa; Prats, Michael I.
Abstract : Objectives: Ultrasound is a valuable tool for anatomy education, but limited evidence exists for using ultrasound to teach neuroanatomy and neurophysiology. Previous work demonstrated a potential increase in medical knowledge in preclinical medical students participating in a neurology ultrasound workshop, however, without comparison to a control group. After 2 years, we assessed how a neurology ultrasound workshop affected the medical knowledge of participating preclinical medical students compared to a traditional curriculum control group. Methods: This quasiexperimental study compared academic performance of ultrasound workshop participants to nonparticipant classmates. The primary outcome was the overall neurologic disorders unit total score. An analysis of covariance was conducted to test for statistically significant differences while controlling for the average quiz score. Results: A total of 360 medical students were included in the study. The intervention group (n = 57) showed no significant difference in the total unit score ( F  = 3.206; P  = .074), with averages for the control and experimental groups being 87.3% ± 5.0% and 88.4% ± 4.8%, respectively. Additionally, anatomy practical scores and written final examination scores were not significantly different between groups ( F  = 1.035; P  = .310; F = 2.035; P  = .155). Conclusions: Participation in a neurologic disorders ultrasound workshop did not appear to be correlated with improved curricular performance in our cohort. Further research should continue to assess ultrasound workshops in other organ systems to elucidate the relationship between learning ultrasound and the impact on medical school academic performance.